Histopathology of Polymicrogyria - Iga Fudyma; Nitin R. Wadhwani (Pediatric Neurology Briefs Publishers, 2015)
Investigators from Sainte Justine Hospital (Montreal), Montreal Neurological Hospital and Institute, King's College Hospital (London), and John Radcliffe Hospital (Oxford) retrospectively reviewed medical records, autopsy reports, and genetic studies containing "Polymicrogyria."